The effect of Problem-based Learning (PBL) with mockup media in learning programmable logic controller - Suhanto Suhanto; Mustaji Mustaji; Moch. Rifai; Lady Silk Moonlight; Asep Muhamad Soleh; Ahmad Fudholi (Jurnal Pendidikan Vokasi, 2024)
This research aims to (1) examine the differences in learning outcomes of programmable logic controllers between cadets who use problem-based learning strategies assisted by mockup media and problem-based learning strategies, (2) examine the differences in learning outcomes of programmable logic controllers between cadets who have high and low initial abilities, and (3) examine the interaction effect between learning strategies and initial abilities on learning outcomes of programmable logic controllers. This research uses a 2 x 2 factorial design with the object of research being the 3rd-semester airport electrical engineering study program students at Aviation Polytechnic Surabaya. The sample of this research includes 47 students of the TLB 11 AB class as the experimental group of problem-based learning strategy assisted by mockup media and 46 students of the TLB 12AB class as the control group of problem-based learning strategy. A learning outcomes test collected the data on learning outcomes in the form of multiple choice. Learning outcomes data were analyzed using two-tailed ANOVA (analysis of variance). The results showed that there is a significant difference in learning outcomes of the programmable logic controller between cadets who learn using problem-based learning assisted by mockup media and problem-based learning, there is a significant difference in learning outcomes of the programmable logic controller between cadets who have high and low initial abilities, there is no interaction effect between learning strategies and cadets' initial abilities on learning outcomes of the programmable logic controller. This research can contribute to improving students' understanding and skills in the field of PLC. Through practical experience and relevant projects, students can develop a deeper understanding of PLC concepts and improve their technical skills in designing, implementing, and solving problems related to PLC systems.